2020
DOI: 10.3390/su12104127
|View full text |Cite
|
Sign up to set email alerts
|

Youth Mobilization to Stop Global Climate Change: Narratives and Impact

Abstract: Galvanized by Greta Thunberg’s idea for Friday school strikes, “climate strikes” emerged in 2018 and 2019 as a form of youth social movement demanding far-reaching action on climate change. Youths have taken various actions to combat climate change, but academics have not paid sufficient attention to youth climate mobilization. This study thus examines the questions of what has motivated youth to mobilize and how they have shaped global climate politics and governance. This study focuses particularly on the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
143
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(154 citation statements)
references
References 63 publications
2
143
1
8
Order By: Relevance
“…Although there are plausible in-groups and out-groups in the context of climate change (e.g., age groups, environmentalists vs. non-environmentalists, and nations that vary with respect to their contribution and vulnerability), research has yet to identify the groups that are theoretically and practically most relevant for those involved in activism. It is also not yet determined that a "perpetrator" out-group is a requirement for motivating collective action [20,25] (but see [10], which suggests the presence of a victim vs. perpetrator narrative within the youth climate movement). Our findings would suggest that, for climate change, this is not necessarily so, although we must interpret the lack of a significant finding in the case of anger and moral conviction with some caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are plausible in-groups and out-groups in the context of climate change (e.g., age groups, environmentalists vs. non-environmentalists, and nations that vary with respect to their contribution and vulnerability), research has yet to identify the groups that are theoretically and practically most relevant for those involved in activism. It is also not yet determined that a "perpetrator" out-group is a requirement for motivating collective action [20,25] (but see [10], which suggests the presence of a victim vs. perpetrator narrative within the youth climate movement). Our findings would suggest that, for climate change, this is not necessarily so, although we must interpret the lack of a significant finding in the case of anger and moral conviction with some caution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has investigated what motivates people to take personal action on climate change [5,6] and why they participate in collective action in general [7][8][9]. However, little is known about the motivations of climate change strikers; in particular, why young people have joined this most recent wave of strikes (for a notable exception, see Han and Ahn's narrative analysis [10]). While concern about climate change can be considered an intuitive and reasonable explanation for such participation, previous research also draws attention to a range of other relevant factors influencing people's involvement in protest, including a person's moral convictions, how they see themselves in relation to a social movement, and their emotional investment in it [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey done in the United States, for example, found that climate change is seen as an extremely important issue for six in ten teenagers and that teens and young adults are 10 percentage points more likely than adults to say that climate change will cause a great deal of harm to people in their generation (Hamel et al 2019). This concern is also evident from the growing number of young people joining environmental movements globally, and demanding action on climate change and biodiversity loss (Han and Ahn 2020;Marris 2019;O'Brien et al 2018). However, many young people are also left wondering about effective solutions to global problems.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Holmberg and Alvinius noted that "there is very little research on children's resistance in relation to global issues" [3] (p. 2). In 2020, still "few academic analyses have addressed the mobilization of youth in global climate politics" [4] (p. 1). Current analyses focus on the formal features of the climate social movement, the types of activism and forms of dissent [5], the type of claims and counterclaims that are made, and the use social media [3,4], or the different narratives specific to the global North/South [6].…”
Section: Introductionmentioning
confidence: 99%